HUBUNGAN ANTARA BEBAN KERJA MENTAL DAN DURASI KERJA DENGAN KEJADIAN HUMAN ERROR PADA PETUGAS AIR TRAFFIC CONTROL (STUDI KASUS DI JAKARTA AIR TRAFFIC SERVICES CENTER – AIRNAV INDONESIA) - Senjaya, Mahdia Noer Adiba; Wahyuni, Ida; Widjasena, Baju (Jurnal Kesehatan Masyarakat (Undip), 2020)
Human error is not the sole cause of an accident because the cause of an accident is multifactor (multiple causes), but it is estimated that its contribution is very large in an accident. According to the theory of the Human Factor Analysis and Classification System (HFACS), human error shows that there are 4 (four) levels of failure. In this study the focus is on factors that are below the level of unsafe officer action that can cause errors, including the personal factors of the officer (age, education, years of work), work demands (duration of work) and the mental condition of the officer (mental workload). ATC officers requires discipline, high concentration, accuracy to ensure the safety of users of aviation services. The purpose of this study was to analyze the relationship between age, education, years of work, duration of work, and mental workload with human error occurrence towards ATC officers at the Jakarta Air Traffic Services Center - Airnav Indonesia. This study used cross sectional research design. Sampling method used in this study was accidental sampling with the Lameshow formula and obtained as many as 72 people. NASA-TLX and questionnaire were instruments of this research. Based on statistical tests of the relationship with Rank Spearman (p value = 0.024) showed that there was a relation between mental workload and work duration with human error occurrence. The researcher advised the company to create an effective crew resource management (CRM) among the ATC officers on duty as error management.